Youth Ministry : Revised Edition - Kaster, Jeffrey (Book collections on Project MUSE., 2016)
All church ministries are oriented toward fostering missionary discipleship. Youth ministry focuses this mission on young people. In this new book in the Collegeville Ministry series, Jeffrey Kaster explores leadership for youth ministry, Christian discipleship, conversion, the theological foundations for youth ministry, the importance of community and belonging, and vocational discernment. Kaster looks at the practice of vocational discernment and how it encourages youth ministry to continually help young people discern their gifts, connect them in service to meet the world's deep needs, and foster Christian discipleship. Youth ministry at its best mobilizes the faith community to support young people as they learn to live as disciples of Jesus Christ. The Collegeville Ministry series provides practical, effective help for those serving the parish through various ministries, and comprehensive training on the various liturgical roles. Each work is prepared by a specialist in the field and provides down to earth suggestions for making ministry more meaningful for the ministers and those they serve.